Literasi Keuangan Dan Toleransi Risiko Terhadap Keputusan Investasi Anggota Galeri Investasi Bursa Efek Indonesia Fakultas Ekonomi Dan Bisnis Universitas Negeri Padang - Alrahmanto; Laynita Sari; Dewi Zulvia (Penerbit Jurnal Indonesia, 2025)
The objective of this study is to determine whether financial literacy and risk tolerance influence investment decisions at the Investment Gallery of the Indonesia Stock Exchange, Faculty of Economics and Business, Universitas Negeri Padang. This research employs a quantitative approach, with the study's subjects being members of GIBEI FEB UNP from the 2021–2023 cohorts, totaling 38 individuals. Data were collected through questionnaires distributed to GIBEI FEB UNP members. Data processing was conducted using SPSS version 26. The results of this study indicate that financial literacy has a positive and significant effect on investment decisions, whereas risk tolerance does not affect investment decisions.